The Islamic Reformist Movement in the Malay-Indonesia World in the First Four Decades of the 20th Century: Insights Gained from a Comparative Look at Egypt - Giora Eliraz (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
The transmission of Islamic reformist ideas from the Middle East, in particular from Egypt, to the Malay-Indonesian world stimulates interest in observing and examining this formative chapter in the history of the Islamic reformist movement in the Malay-Indonesian world by taking a comparative look at Egypt. Similarly, an observer of both the center of Islamic world and its